2001
DOI: 10.1159/000055745
|View full text |Cite
|
Sign up to set email alerts
|

Distant Metastases from Oropharyngeal Cancer

Abstract: Distant metastasis is a significant problem in patients with carcinoma of the oropharynx, occurring in approximately 15–20% off all patients over the course of the disease. It is, however, a relatively uncommon first site of failure, as compared to local and regional recurrence. Distant spread occurs most commonly to the lungs, in patients who present with advanced disease, and especially in those with pathologically proven lymph nodes at multiple levels of the neck or in the lower neck. Metastasis to distant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 7 publications
2
9
0
Order By: Relevance
“…Locoregional control is a well-established predictor for the development of DM in SCC of the oropharynx and other head and neck sites 1618 but we also found it to be a significant factor for survival with already established DM. The loco-regional control rate was significantly better in the p16-positive group with DM.…”
Section: Discussionmentioning
confidence: 48%
“…Locoregional control is a well-established predictor for the development of DM in SCC of the oropharynx and other head and neck sites 1618 but we also found it to be a significant factor for survival with already established DM. The loco-regional control rate was significantly better in the p16-positive group with DM.…”
Section: Discussionmentioning
confidence: 48%
“…Head and neck cancer (HNC) is one of the 10 most common malignancies worldwide 1. Previous studies have shown that approximately 20% of patients with HNC have distant metastases and second primary cancers, with lung, bone, and liver being the most frequent distant sites 2–4. HNC is classified according to the TNM staging system, and treatment and prognosis are modified when distant malignancies are present.…”
Section: Introductionmentioning
confidence: 99%
“…It is an aggressive disease with metastasis having been reported in up to 15–20% of cases, with lungs, bone and liver being common sites 2. Although cutaneous metastasis occurs in <1% of patients,3 several large studies (the largest having 100 453 patients) on cutaneous metastasis have shown that up to 9% of all cutaneous metastasis occur from head and neck malignancies, the majority of which were squamous cell carcinoma4—implying that, in cutaneous metastasis from an unknown primary, head and neck malignancies are important primaries to be considered.…”
Section: Discussionmentioning
confidence: 99%